Global and regional pulse economies: Current trends and outlook - Joshi, Pramod Kumar; Rao, P. Parthasarathy (International Food Policy Research Institute, 2016)
The pulse sector is undergoing dynamic changes globally and in several regions and countries to meet the challenge of growing demand in the face of sluggish production growth. Realizing the importance of pulses in the human diet, 2016 has been declared the International Year of Pulses (IYP). This report captures the dynamics of the pulse sector during the last three decades. The examination of pulse supply, demand, uses, trade, prices, and outlook would help researchers and policy makers make more informed decisions related to the sector. Pulse-based food is an important source of dietary protein and essential minerals, particularly for the vegetarian population. At the global level, the average share of pulses is only 5 percent of the total protein consumption but their contribution in several developing countries range between 10 and 40 percent. To meet the growing demand and raise their per capita availability, countries made efforts to increase production and explore trade opportunities to augment domestic supply. Overall between 1980 and 2013, pulses production at the global level grew at an annual rate of 1.3 percent but there were, however, two phases of pulses production at the global level. While there was almost a period of stagnation in production of pulses during the1990s, production has sharply increased since 2005. The bulk of the increase in production came from developing countries where both area and yield growth (from a low base) contributed to the production. For developed countries—where production also grew—the center of production shifted from Europe to North America and Oceania. For developing countries, two new centers of production emerged in Eastern Africa and Southeastern Asia (Myanmar).